2021
DOI: 10.1002/yea.3565
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the response to metal ions and nonsense‐mediated mRNA decay across different Saccharomyces cerevisiae genetic backgrounds

Abstract: Regulation of mRNA steady‐state levels is important in controlling gene expression particularly in response to environmental stimuli. This allows cells to rapidly respond to environment changes. The highly conserved nonsense‐mediated mRNA decay (NMD) pathway was initially identified as a pathway that degrades aberrant mRNAs. NMD is now recognized as a pathway with additional functions including precisely regulating the expression of select natural mRNAs. Majority of these natural mRNAs encode fully functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Furthermore, under elevated copper levels, metallothioneins such as CUP1 and CRS5 , and additional genes involved in adaptation to high copper levels are elevated (Figure 1B). We have reported previously that wild-type and NMD mutant yeast strains tolerate high copper levels with the NMD mutants being more tolerant than the wild-type strains (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, under elevated copper levels, metallothioneins such as CUP1 and CRS5 , and additional genes involved in adaptation to high copper levels are elevated (Figure 1B). We have reported previously that wild-type and NMD mutant yeast strains tolerate high copper levels with the NMD mutants being more tolerant than the wild-type strains (35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we would anticipate the MAC1 mRNA would be stabilized in wild-type yeast strains under this specific growth condition when higher levels of copper are required. Our previous analysis of mRNAs encoding proteins involved in various aspects of copper homeostasis, demonstrated that regulation of these mRNAs by NMD could be responsive to fluctuations in environmental copper levels and generates physiological consequences to the yeast cells (17,24).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PCA1 encodes a cadmium efflux transporter. Whereas some natural S. cerevisiae isolates harbor a functional PCA1 gene that confers cadmium resistance, most laboratory S. cerevisiae strains including CEN.PK2-1c used in this study contain a nonfunctional Pca1p due to a G970R missense mutation (Adle et al, 2007;Wei et al, 2014;Wong et al, 2021). Therefore, it is unlikely to identify PCA1 as a positive hit via genome-scale screening using a CEN.PK cDNA-derived overexpression library.…”
Section: Discussionmentioning
confidence: 99%
“…PCA1 mRNA is also regulated by NMD and involved in the protection of the cell from metal toxicity (Guan et al 2006 ; Wong et al 2021 ) PCA1 is an evolutionarily conserved P 1B -type cation-transporting ATPase that is widely distributed from bacteria to humans (Rad et al 1994 ). PCA1 has been proposed to be involved in copper and iron homeostasis (De Freitas et al 2004 ; Rad et al 1994 ).…”
Section: The Role Nmd Plays In Copper Homeostasismentioning
confidence: 99%
“…The protein encoded by CAD2 functions in the cadmium efflux system of yeast cells (hereafter referred as PCA1 970G ). The PCA1 allele found in most common lab yeast strains possess a missense mutation in the ATP-binding residue conserved in P 1B -type ATPases [hereafter referred as PCA1 970R ; (Adle et al 2007 ; Wong et al 2021 )]. In humans, a substitution in the ATP7B similar to the one found in PCA1 leads to Wilson's disease.…”
Section: The Role Nmd Plays In Copper Homeostasismentioning
confidence: 99%